2021
DOI: 10.1186/s13099-021-00474-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide association study identified candidate genes associated with gut microbiota

Abstract: Background Gut microbiota is closely associated with host health and disease occurrence. Host genetic factor plays an important role in shaping gut microbial communities. The specific mechanism of host-regulated gene expression affecting gut microbiota has not been elucidated yet. Here we conducted a transcriptome-wide association study (TWAS) for gut microbiota by leveraging expression imputation from large-scale GWAS data sets. Results TWAS detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
(62 reference statements)
1
7
0
Order By: Relevance
“…The lack of an association between the infant microbiota and maternal FUT2 genotype at two months of lactation suggests that the oligosaccharides provided by the mother were sufficiently equivalent or were overshadowed by the glycans provided by the gut mucosa of the infant. The finding that infant FUT2 status significantly impacted their microbiome is consistent with other studies on the FUT2 genotype and microbiome, which have typically been conducted in adult populations, including studies on healthy individuals and studies on gut and respiratory diseases [ 21 , 28 , 29 , 36 ]. However, the literature on FUT2 and the microbiome remains controversial, as diverse, large-scale studies have reported differing results [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The lack of an association between the infant microbiota and maternal FUT2 genotype at two months of lactation suggests that the oligosaccharides provided by the mother were sufficiently equivalent or were overshadowed by the glycans provided by the gut mucosa of the infant. The finding that infant FUT2 status significantly impacted their microbiome is consistent with other studies on the FUT2 genotype and microbiome, which have typically been conducted in adult populations, including studies on healthy individuals and studies on gut and respiratory diseases [ 21 , 28 , 29 , 36 ]. However, the literature on FUT2 and the microbiome remains controversial, as diverse, large-scale studies have reported differing results [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
“…Statistical analyses were performed using ASV tables generated through the outputs of Kraken2/Bracken [ 33 , 34 ] or HUMAnN2 [ 35 ] after converting the read counts to relative abundance. Alpha- and beta-diversity were determined using the vegan package, and LEfSe was determined by using the MicrobiomeMarker [ 36 ] package in R. Alpha-diversity was calculated as Shannon diversity and beta-diversity was calculated as Bray–Curtis distance.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in the abundance of some bacteria have been used as biomarkers to screen for IBD and other gastrointestinal diseases [ 94 96 ]. A TWAS conducted in the gut microbiota has detected multiple tissue-specific candidate genes in the sigmoid and transverse colon, respectively, such as TOB2P1 for Enterococcaceae in sigmoid colon, WDR6 for Coprococcus in sigmoid colon, and KCNIP3 for Veillonellaceae in transverse colon [ 97 ]. An association study using bioinformatic analysis in colorectal cancer also observed two overlapping pathways, the bile secretion and steroid hormone biosynthesis pathways, enriched by operational taxonomic units (OTUs) and gene expression patterns in colon tissue, respectively [ 98 ].…”
Section: Heterogeneity Of Various Tissue Types Selected In Eqtlmentioning
confidence: 99%
“…These analyses offer the benefit of increasing the power to detect associations, due to a 50-fold reduction in multiple testing compared to GWAS [15]. While TWAS have been successful in identifying novel biology underlying diseases, including but not limited to, kidney diseases, rheumatoid arthritis, depression and gut microbiota [16][17][18][19], the complex patterns of linkage disequilibrium (LD) in the genome can complicate the identification of causal genes [20]. Therefore, fine-mapping strategies, which are performed to identify causal genes and variants, are an essential component of TWAS analyses [21].…”
Section: Introductionmentioning
confidence: 99%